PENILAIAN KINERJA SOSIAL BERBASIS MAQASID SYARIAH PADA BANK UMUM SYARIAH HASIL KONVERSI DI INDONESIA - Siti Amaroh (MALIA: Journal of Islamic Banking and Finance, 2018)
This paper aims to evaluate the social performance based on maqasid shariah of Islamic banks from conversion mode in Indonesia during the period 20142017. The data was obtained from Islamic banks’ annual report that was validated by Bank Indonesia and Financial Services Authority. Maqasid shariah model in this study was developed by Abdul Majid Najjar with used 4 objectives and 8 dimensions and then referred by some researchers with some elements and measurements. This research is using 23 elements and derived into 19 ratios and 46 statements to determine scores of each objectives. The result showed several findings. Bank Panin Syariah achieved the highest scores of safeguarding human value (1st objective) during the period 2015-2017. Bank Central Asia Syariah reached the highest scores of safageuarding human self (2nd objective) during the period 2015-2017. Bank Mega Syariah Indonesia attained the highest scores of safeguarding for society (3rd objective) during the period 2014-2017. Bank Syariah Mandiri gained the highest score of safeguarding physical environment (4th objective) for the period 2014, 2016, and 2017. The highest total score for the overall objective is achieved by Bank Mega Syariah Indonesia during the period 2015-2017.